Wages and Employment in the Netherlands, 2017-2023 - Iris Klinker; Bas ter Weel (Institute of Labor Economics (IZA), 2024)
This research documents changes in employment and wages in the Netherlands for different types of workers. We compare 2017 to 2023 using regression-adjusted wages to make sure changes in composition of the workforce do not influence our estimates. The research period has been characterised by high labour demand, negative supply shocks, high levels of inflation and economic lockdowns, all of which have contributed to substantial labour-market dynamics. Our findings suggest that employment has been growing by 2 percent in the period 2017-2023, of which 1.8 percent has been due to additional workers finding employment. Women have experienced the largest increase in employment, while the employment of men on temporary contracts has slightly fallen. Wages have been rising for workers at the bottom of the wage distribution. From the median of the wage distribution onwards real gross hourly wages have been fallen. The most likely explanation for rising wages at the bottom is the stepwise increase in minimum wages enforced by new labour-market legislation.
Keywords: E24; E31; J21; J31; 330; employment; inflation; wages; COVID-19